Prosthodontics: Technical Approaches to the Fabrication and Cementation of IPS Empress II e Max Porcelain Veneers, Bridges and Onlays - Dr. Evangelos V. Gkogkas (Prosthodontics: Technical Approaches to the Fabrication and Cementation of IPS Empress II e Max Porcelain Veneers, Bridges and Onlays, Edition 1, 2025)
The tooth functions as a complex organ with distinct anatomical, physiological, and functional characteristics, making it vulnerable to various pathologies influenced by the oral environment, particularly due to bacterial colonization. In prosthodontics, lithium disilicate ceramics, specifically IPS Empress II e max, provide high-strength, aesthetic options for restorative treatments. This book systematically examines the process of selecting an optimal cement, adhering to manufacturer-recommended cementation protocols, and evaluates materials through comprehensive research methodologies. The findings offer evidence-based insights for clinicians engaged in aesthetic dentistry, facilitating informed decision-making. All materials and methods were tested on human natural teeth without caries or necrosis, the closest it could be to an in-vivo method. Furthermore, the book addresses the clinical considerations surrounding cemented versus screw-retained restorations in implant prosthodontics. The final section includes detailed case studies that illustrate strategies for smile rehabilitation and minimally invasive approaches, providing practical guidance for daily clinical applications. Scientists can find a path of the Philosophy about how we deal with Smile Rehabilitation and a minimally invasive approach to a daily clinical problem for our patients.